Ilizarov-Assisted Reduction of Femoral Condyle Locked in Tibial Fracture: A Case Report - Anteshwar Birajdar; Sushant Kumar; Setu Kaneria; Archit Gupta; Omkar Shinde; Sagar Gurnani (Journal of Orthopaedic Case Reports)
Introduction: Tibial plateau fractures are commonly managed using open reduction and internal fixation (ORIF) techniques. However, external fixation through minimally invasive methods has emerged as an excellent alternative, especially for complex fracture patterns. This study focuses on evaluating the clinical and radiological outcomes of Schatzker type V tibial plateau fractures treated using the Ilizarov external fixator, highlighting its safety, effectiveness, and potential advantages over traditional approaches. Case Report: A 38-year-old male presented to the emergency department following a road traffic accident, complaining of acute pain and tenderness over his left knee, which had persisted for 12 h. Radiographic examination revealed a left tibial plateau fracture classified as Schatzker type V. Given the complexity of the fracture, the Ilizarov external fixator was selected as the treatment method. The procedure aimed to achieve stable fixation while minimizing soft-tissue damage, promoting early mobilization, and reducing the risk of complications. Conclusion: The Ilizarov technique proved to be a safe and effective treatment option for managing proximal tibial fractures of the Schatzker type V variety. Its minimally invasive nature is associated with low morbidity, making it a reliable alternative to traditional ORIF, especially in complex cases. The clinical and radiological evaluations confirmed satisfactory outcomes, reinforcing the utility of the Ilizarov method in complex tibial plateau fractures.